Influence of product selling price on purchasing decisions at MSMEs global accessories and toys Ciapus Bogor Regency with product quality as a mod-erating variable - I Gede Marendra; I Made Aryata (Law and Economics, 2026)
Micro, Small, and Medium Enterprises (MSMEs or UMKM) are a strategic sector that plays a crucial role in driving national economic growth, including in Bogor Regency. Increasing competition in the creative industry has caused sales of Global Accessories & Toys products to fluctuate quarterly compared to year-on-year from a marketing perspective, product quality and price are two main determinants that influence consumer behavior, especially in the purchasing decisions-making process. The research used a quantitative method using the Structural Equation Modeling (SEM) method, with a sample size of 150 respondents. The SEM analysis stages include: Normality Test, Validity Test, Reliability Test, Moderation Test, Hypothesis Test, and Goodness of Fit Test. Based on the results of the research conducted, it is known that Price has a significant influence on Purchasing Decisions, this can be seen from the p-value of 0.000 so that Ho1 is accepted, while Product Quality does not affect Purchasing Decisions, this can be seen from the p-value of 0.183 so that Ho2 is accepted. However, Product Quality weakens the influence of Price on Purchasing Decisions, this can be seen from the p-value of 0.888 so that Ho3 is accepted.